Investigating the Relationship between Attitudes towards Drug Addiction and Personality Traits in Abadan University of Medical Sciences Students in 2019 - Otbeh, Mehdi; Zahedi, Atefeh; Rastegarimehr, Babak; Maboubi, Mohammad (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Different personality traits have different positive or negative attitudes towards addiction. This study examines the association between the attitude towards drug addiction and the personality characteristics of Abadan University of Medical Sciences students and highlights the social issue of drug addiction due to its ability to undermine social beliefs. Methods: In this cross-sectional study, 324 students were included in the research using the random sampling method. The target population was students, and the research sample was students of Abadan University of Medical Sciences. The data collection tools were two questionnaires: "attitude towards drug addiction" and questionnaire of the "five-factor model of personality". Tests of Student -t test, one way ANOVA and linear regression were used to analyze the data. Results: The study participants included 107 men and 217 women. Most of the participants (93.2%) were single. The average age of the participants was 22.25 ± 6.35 years. The mean and standard deviation of attitude towards addiction in students were 59.08±17.34 which was lower than the median value of the questionnaire (96), and this difference was statistically significant. (P value<0.001). Addiction attitude was positively correlated with neuroticism domain (r=0.13, P < 0.05) and negatively correlated with openness to experience (r=-0.31, P < 0.01). According to the results of the regression test, 14% of the changes in attitudes towards addiction were predicted by personality domains. Also, neuroticism and openness to experience were the most important predictors for attitude towards addiction. Conclusions: Personality traits, especially neuroticism, are predictors for attitudes toward drug addiction and drug abuse. Counseling centers should collect student personality traits to predict drug addiction attitudes, identify vulnerable individuals, offer counseling and educational services, and organize events. Participating in sports, attending lectures, and social skills training can reduce drug abuse. Authorities should adapt educational programs to student characteristics.